The stars are fire - Shreve, Anita (Alfred A. Knopf, 2017)
"In October, 1947, after a summer-long drought, fires began near Bar Harbor and raced along the coast of Maine, ravaging two hundred thousand acres--the largest fire in Maine's history. In the southern part of the state, people were forced into the sea to escape the flames. Five months pregnant, Grace Holland is left alone to protect her two toddlers when her husband Gene joins the volunteers fighting to bring the fire under control. Along with her best friend, Rosie, and Rosie's two young children, the women watch in horror as their houses go up in flames, then walk into the ocean as a last resort. They spend the night frantically trying to save their children. When dawn comes, they have miraculously survived, but their lives are forever changed: homeless, penniless, and left to face an uncertain future in a town that no longer exists. As Grace awaits news of her husband's fate, she is thrust into a new world in which she must make a life on her own, beginning with absolutely nothing--she must find work, a home, a way to provide for her children. In the midst of devastating loss, Grace discovers glorious new freedoms--joys and triumphs she could never have expected her narrow life with Gene could contain--and her spirit soars. And then the unthinkable happens, and Grace's bravery is tested as never before."--